Morphological and Genetic Variation of Three-spined Stickleback (Gasterosteus aculeatus) in a Hybrid Zone - Bodkin, Harry (2025)
The mechanisms that contribute to evolutionary divergence between popula-tions are difficult to discern, but may be suggested by patterns in the distribu-tion of morphological traits, alleles and genotypes. Hybrid zones across eco-tones and population variation across environmental gradients can be especial-ly useful in this regard. Here, I analyse changes in morphological traits such as armour plating, standard length and body shape, as well as genetic variation such as the allele frequency of the well-known Eda locus, across environmental gradients within a hybrid zone and between systems. I show the lack of a pat-tern in morphological traits across the hybrid zone, but very strong genetic structure. In addition, I observe allele frequencies of chromosomal inversions across environmental gradients to show a tight link between the chromosome XI inversion and pH in freshwater systems.